Lifewide Learning for Early Reading Development. Issue 155 (March 2017) - Dowd, Amy Jo; Friedlander, Elliott; Jonason, Christine; Leer, Jane; Sorensen, Lisa Zook; Guajardo, Jarrett; D'Sa, Nikhit; Pava, Clara; Pisani, Lauren
Abstract: The authors examine the relationships between children's reading abilities and the enabling environment for learning in the context of Save the Children's Literacy Boost program. They conceptualize the enabling environment at a micro level, with two components: the home literacy environment, represented by reading materials/habits at home, and the community learning environment (community reading activities). Using longitudinal reading scores of 6, 874 students in 424 schools in 12 sites across Africa and Asia, there was 1) a modest but consistent relationship between students' home literacy environments and reading scores, and 2) a strong relationship between reading gains and participation in community reading activities, suggesting that interventions should consider both home and community learning environments and their differential influences on interventions across different low‐resource settings.